Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka Provinsi NTB Tahun 2020-2022 - Phyta Rahima; Irwan Cahyadi; Isra Dewi Kuntary Ibrahim; Adrianda Anwar (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to determine the factors that influence the open unemployment rate in Mataram city at 2020 - 2022. The research method used in this study is a type of quantitative method. The panel data used in this study were processed using Microsoft Excel and Stata 14. This study used panel data regression analysis with a random-effect model. The results of the study show that the labor force and education level have a significant effect on the open unemployment rate in districts/cities in the Province of NTB 2020 - 2022. On the other hand, the minimum wage and economic growth show insignificant results. Minimum wages, labor force, and economic growth have a negative effect on the unemployment rate in Mataram City in 2020 - 2022, while the level of education has a positive effect. Simultaneously the minimum wage, labor force, economic growth, and education level also have a significant effect on the open unemployment rate in Mataram City in 2020 - 2022